2013
DOI: 10.5301/ejo.5000294
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatism Prevalence and Biometric Analysis in Normal Population

Abstract: Abstract:Introduction: Our aim was to analyze the magnitude, the orientation and the agerelated changes of corneal astigmatism and its correlation with biometric parameters in healthy eyes. Patients and methods: Patients over 15 years were enrolled in our study. Exclusion criteria were previous ocular surgery, corneal disease or contact lens wearing. Axial length (AL), keratometric readings and anterior chamber depth (ACD) were assessed using IOLMaster. Results: In our study 1092 eyes were examined. Abstract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
36
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 29 publications
10
36
1
3
Order By: Relevance
“…By contrast, the percentage of WTR astigmatism decreased with age. These findings are generally consistent with those of previous studies [7, 13, 15, 16]. …”
Section: Discussionsupporting
confidence: 93%
“…By contrast, the percentage of WTR astigmatism decreased with age. These findings are generally consistent with those of previous studies [7, 13, 15, 16]. …”
Section: Discussionsupporting
confidence: 93%
“…By contrast, the percentage of WTR astigmatism decreased with age. These findings are consistent with the characteristics seen in populations from different countries and regions [6, 9, 27, 28]. These changes have been found to be due to a discrepancy in eyelid morphology and power [29].…”
Section: Discussionsupporting
confidence: 89%
“…Studies suggest that CA orientation may change with age, and WTR, common in young children, gradually shifts to ATR and OBL as age increases. 33,34 IA has been attributed to the refracting power of the lens, posterior cornea, and errors in optical centration. Some studies have concluded that CA exceeds TA by 0.5 D on average and that no internal compensation for CA exists.…”
Section: Discussionmentioning
confidence: 99%